The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1104/pp.50.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Phytochrome-enhanced Geotropic Sensitivity to Ethylene Production

Abstract: Brief exposure of etiolated pea (Pisum sativum cv. Alaska) seedlings to red light enhances subsequent development of geotropic curvature of the stem. Both this response and inhibition of ethylene production by red light become maximal 8 hours after illumination. Very low concentrations of applied ethylene inhibit development of geotropic curvature, whereas hypobaric treatment enhances geotropic sensitivity by removing endogenous ethylene. Increased geotropic sensitivity after illumination is accompanied by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
24
4

Year Published

1980
1980
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 20 publications
6
24
4
Order By: Relevance
“…It has recently been reported that light inhibits ethylene production in segments of green oat leaves but not in etiolated leaves (7). The experiments dealing with the effect of monochromatic light on plant tissues suggest an inhibitory effect of red light as compared to darkness on the rate of ethylene production (8,11,12,18). However, Janes et al (10) found no effect of red light on the rate of ethylene production in the intact lettuce seedlings.…”
Section: Discussionmentioning
confidence: 87%
“…It has recently been reported that light inhibits ethylene production in segments of green oat leaves but not in etiolated leaves (7). The experiments dealing with the effect of monochromatic light on plant tissues suggest an inhibitory effect of red light as compared to darkness on the rate of ethylene production (8,11,12,18). However, Janes et al (10) found no effect of red light on the rate of ethylene production in the intact lettuce seedlings.…”
Section: Discussionmentioning
confidence: 87%
“…Although most reports related that white or red light inhibited ethylene production (5,8,17,19), one report observed that red light promoted ethylene production in the shoot of pea seedling (16). It (2,5,9). Possible involvement of phytochrome in inhibiting ethylene formation in these etiolated hook region by promoting ACC malonylation is currently under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…However, light did not cause any significant increase in the extractable ACC-malonyltransferase activity. A number of reports have shown that light regulated ethylene production which in turn modified plant growth (4,5,9,18,19 m-2 s-'), red light or far-red light. The red and far-red light sources were from a projector equipped with a 650 nm and 730 nm filter, respectively.…”
Section: Abstracitmentioning
confidence: 99%
See 2 more Smart Citations